Influence of Welsh Inversion and Agreement on English Syntax - B. S. Bogdanov; A. А. Shumkov (Дискурс, 2024)
Introduction. Ordering the space and time elements in Welsh independent clause, when the subject is formed from a noun, is accompanied by a rather specific agreement of these elements in number. In the grammars of Welsh one can find various classifications of noninverse and inverse sentences and, mostly, practical notions concerning the peculiarities of the agreement of the main parts. Theoretical explanations are meanwhile quite poor. Because it can be proposed, that the peculiarities of sentence organization in Welsh could influence the syntax of English – the language of international communication, the theme under discussion is rather topical.Methodology and sources. The investigation is carried out on the base of four Welsh grammars, containing large chapters on syntax. We also used a collection of texts, from which the examples of non-inverse and inverse sentences were taken. The methodological base of the work is the binomiality idea.Results and discussion. In non-inverse Welsh sentences, the predicate agrees with the subject in number only in case the subject is formed from a pronoun; in case the subject is formed from a noun, the 3-rd person singular is always used. In mixed and abnormal sentences, the word order becomes inverse. The investigation of explicit elements of subject and predicate has turned to be not sufficient, and we were forced to apply the hypothesis on implicitness, inexplicitness and ellipsis of some elements. In doing so, we managed to match the analytic tense in Welsh with the continuous tense in English. It was also suggested, that (emphatic) Welsh constructions can influence the structure of English sentence.Conclusion. In Welsh independent clauses, the weak space specifier can be modified by an implicit strong pronominal semifinitive, after what an implicit element in function of the space element reveals in the subject. Developing the hypothesis about the possible inexplicitness of fixed semifinitives in the Welsh subject, we can also assume that abnormal and mixed sentences in Welsh originate from the subordinate clause of a complex sentence. Within the framework of the general model, it turns out that the arrangement of space and time elements does not contradict the Indo-European system, which fully manifests itself in the English sentence.